Closing the gap - Detection of clinically relevant von Willebrand disease in emergency settings through an improved algorithm based on rotational Thromboelastometry 11 Medical and Health Sciences 1103 Clinical Sciences 11 Medical and Health Sciences 1102 Cardiorespiratory Medicine and Haematology - Topf, H. -G.; Strasser, Erwin; Breuer, Georg; Rascher, Wolfgang; Rauh, Manfred; Fahlbusch, F. B. (BMC Anesthesiology, 2019)
Background: Hemorrhage and blood loss are still among the main causes of preventable death. Global hemostatic assays are useful point-of-care test (POCT) devices to rapidly detect cumulative effects of plasma factors and platelets on coagulation. Thromboelastography (TEG) and Thromboelastometry (ROTEM) are established methods in many anesthesiological departments for guided hemostatic treatment. However, von Willebrand disease remains undetected by standard ROTEM, especially during emergency care, despite being the most prevalent congenital hemostatic disorder. Methods: In our monocentric cohort pilot study we focused on hemostatic challenges associated with von Willebrand disease. Twenty-seven patients with suspected von Willebrand disease were included. We modified the routine ROTEM assay by adding a preincubation with ristocetin and commercially available plasma-derived von Willebrand factor to identify clinically relevant von Willebrand disease (VWD). Results: Addition of von Willebrand factor to the ristocetin assay of a VWD type 3 patient restored the reaction of the whole blood probe to match the response of a healthy person. Our modified ROTEM assay with ristocetin (Ricotem) showed that all high responders (n = 7) had VWD. In the low responder group (n = 16) - 10 of 16 had VWD and in the normal responder group (n = 5), 2 of 5 had mild type 1 VWD. Conclusions: This new modification of the standard ROTEM assay enables the detection of otherwise unnoticed critical von Willebrand disease based on alterations in clot formation and might serve as a novel approach to reliably assess severe VWD patients by platelet-mediated blood clotting in an emergency setting. We recommend incorporating this new VWD-focused screening tool into the current ROTEM-based management algorithm of acute microvascular bleeding.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Bleeding; Emergency; ROTEM; Thromboelastometry; Von Willebrand disease; VWD